Helicopter controlling and balancing - Khuong, Kien Trung. (2010)
The Cerebellar Model Articulation Controller (CMAC) is a neural network inspired by the neurophysiologic theory of the cerebellum. The CMAC was rst described by Albus [1, 3] in 1975 and despite its biological relevance, the main reason for using the